Mechanical energy harvesting using piezoelectric polymer for self-powered device application - Kaushik Parida (2018)
The advent of portable electronics has propelled an immense enthusiasm to generate energy from the ambient environment. The availability of mechanical vibrations in the ambient environment is almost everywhere, making it a potential source of energy generation. Various mechanisms have been adopted to tap ambient mechanical vibrational energy. Piezoelectric, triboelectric, and electrostatic mechanisms have been used to convert these ambient mechanical energies into useful electrical energy. Piezoelectric materials have recently gained significant attention to harvest the ambient mechanical energy due to its inherent polarization. Piezoelectric polymers, specifically poly (vinylidene fluoride - trifluoroethylene) [P(VDF-TrFE)], due to its higher piezoelectric coefficient have been extensively explored. Moreover, they can sustain higher stress, strains and strain rates compared to inorganic piezoelectric materials. Additionally, they are flexible, transparent, and chemically stable, thus making it suitable for self-powered device applications. However, the energy harvesting ability of piezoelectric polymers are unsatisfactory and cannot be effectively used to power electronics devices. Extensive effort has been made to enhance the energy harvesting performance of P(VDF-TrFE) films by employing various strategies. The performance can be improved by tuning the fundamental properties such as piezoelectric coefficient, dielectric constant, strain, surface charge, and capacitance. The specific objective of the the work presented in this dissertation is to increase the energy harvesting performance of P(VDF-TrFE) by tuning the structural, surface charge and capacitance of the device. The structural properties of the P(VDF-TrFE) is tuned by a creating porous P(VDF-TrFE) film. The porous P(VDF-TrFE) film showed an increment in the power density by 88 times compared to that of the compact P(VDF-TrFE) film attributed to the lower dielectric constant, higher p phase content and higher compressibility of the porous P(VDF-TrFE) film. A self-charged supercapacitor was demonstrated by utilizing the porous P(VDF-TrFE) film as the separator. Fabrication of the porous P(VDF-TrFE) energy harvester is extremely difficult due to the dielectric breakdown of the porous film on application of an electric field. This problem is circumvented by fabricating a self-poled porous P(VDF-TrFE) sponge, which also eliminates the tedious and costly annealing and poling processes. The output performance of the P(VDF-TrFE) film in the triboelectric energy harvester mode depends on the surface charge density. Enhanced energy harvesting performance of the P(VDF-TrFE) is demonstrated by utilizing the combined effect of triboelectric surface charge and polarization induced surface charge of the self-polarized P(VDF-TrFE) film. The device is used to fabricate a self-powered wide range pressure sensor which can detect pressure ranging from 0.05 to 600 kPa with high sensitivity. Lastly, the capacitance of the device is tuned by using a slime-based ionically conducting current collectors for triboelectric nanogenerator (TENG). The use of ionic current collector leads to the formation of an electric double layer which increases the capacitance of the device thus improving the energy harvesting performance.